INOVASI BIROKRASI PEMERINTAHAN ANTI KORUPSI BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI (MELIHAT KEBIJAKAN E-PROCUREMENT) - Amalia Syauket; Rajanner P. Simarmata; Sri Poedji Lestari (Jurnal Manajemen Publik dan Kebijakan Publik (JMPKP), 2020)
Until the end of 2019, Indonesia's ranking in the International Transparency Anti-Corruption Institute is still stagnant. Has not moved significantly in its ranking. The ranking is based on aspects of the ease of investing in a country. Significant influential factors are bureaucracy and corruption against Indonesia's low ranking. Bureaucracy and corruption are two things that are closely related, especially in carrying out the duties of bureaucrats. Various bureaucratic pathologies have caused bureaucracy to be ineffective and inefficient in carrying out government functions. For this reason, the commitment to eradicate corruption in Indonesia is very important because from the time of Sukarno's administration to Joko Widodo, corruption continued and Indonesia has always ranked first in Asia as the most corrupt country. And spread from Sabang to Merauke.Quite a number of laws and regulations in Indonesia were made as an effort to eradicate corruption. This is a manifestation of the commitment of the Indonesian government to eradicate corruption, but there are still legal loopholes that can be misused by corruptors to escape the law trap. Various attempts have been made by the Government of Indonesia to eradicate corruption, one of which is by establishing an Anti Corruption Agencies. Then in the era of globalization which is characterized by digitalization was taken by the Government to eradicate corruption, which is increasingly massive both from the impact and the actors. This shows that efforts to eradicate corruption along with the progress of information technology, especially based on communication technology (e-Gov).This study was conducted qualitatively using a variety of secondary materials both in the form of literature and internet sources compiled descriptively, with the aim of increasing new understanding of how efforts to eradicate corruption through electronic governance, as one solution in preventing corruption so that Indonesia's competitiveness is improved.